Translation and cultural adaptation of the Computer Vision Syndrome Questionnaire (CVS-Q©) into Italian - Seguí-Crespo, Maria del Mar; Cantó Sancho, Natalia; Ronda, Elena; Colombo, Renzo; Porru, Stefano; Carta, Angela (La Medicina del Lavoro, 2019)
«Translation and cultural adaptation of the Computer Vision Syndrome Questionnaire (CVS-Q©) into Italian». Background: The original Spanish version of the Computer Vision Syndrome Questionnaire (CVS-Q©) is a validated instrument with good psychometric properties to measure the Computer Visual Syndrome (CVS) in workers exposed to video display terminals (VDT). The Italian version would facilitate research and its use in clinical practice the prevention of occupational hazards. Objective: To culturally translate and adapt the CVS-Q© into Italian. Methods: Study with 5 consecutive stages: Direct translation, Synthesis of translations, Retro-translation, Consolidation by a committee of experts and Pre-test. During the Pre-test, a cross-sectional pilot study was conducted on users of VDT (n=40) who completed the Italian version of the questionnaire. Socio-demographic information and exposure assessment to VDT was also collected, as well as on the difficulty to fill in the CVS-Q©. Results: The final version into Italian of the CVS-Q© was obtained. The totality of the sample considered that it didn’t present difficulty in its completion and 90% confirmed that no improvement was needed; so that the 15% required to make changes was not reached. The mean age of participants was of 35.80±16.28 (20-65 years), 57.5% were women and 67.5% used VDT at work. A prevalence of CVS of 62.5% was observed. Conclusion: The CVS-Q© can be considered a tool easy to understand and manage for measuring the CVS in the population exposed to VDT in Italy.